Dissection of the genetic basis and molecular mechanism of ovule number per ovary in oilseed rape (Brassica napus L.) - Qadir, Muslim; Lin, Xinyi; Nabi, Farhan; Ashok, Kishore Kumar; Zhou, Xue-Rong; Sun, Qingbin; Shi, Peiman; Wang, Xinfa; Shi, Jiaqin; Wang, Hanzhong (Frontiers in Plant Science, 2025)
Ovule number per ovary (ONPO) determines the maximum potential of seed number per fruit that is a direct component of seed yield in crops. This study aimed to dissect the genetic basis and molecular mechanism of ONPO using a newly developed doubled haploid (DH) population in oilseed rape. In all the four investigated environments, the ONPO of 201 DH lines exhibited normal distribution with a wide variation from 22.6 to 41.8, suggesting quantitative inheritance appropriate for mapping QTL. A skeleton genetic map of 2111 markers within 19 linkage groups was developed, with a total of 1715.71 cM in length and an average of 0.82 cM between markers. Linkage mapping identified ten QTLs that were distributed on eight chromosomes and explained 7.0-15.9% of the phenotypic variance. Among these, four were identical to the reported and two were repeatedly detected with relatively large effects, highlighting their potential for marker-assisted selection. Phytohormone quantification of ovaries (at the ovule initiation stage) from two pools of high and low ONPO lines showed significant differences in the levels of nine sub-types of phytohormones, suggesting their important roles in regulating ovule number. Transcriptomic analysis identified 7689 differentially expressed genes (DEGs) between the two pools, of which nearly half were enriched into functional categories of reported genes regulating ONPO, including protein, RNA, signalling, miscellaneous, development, hormone metabolism, and tetrapyrrole synthesis. Integration of linkage QTL mapping, transcriptome sequencing and BLAST analysis identified 15 homologues of reported ovule number genes and 327 DEGs in the QTL regions, which were considered as direct and potential candidate genes. These findings propose further insights into the genetic basis and molecular mechanisms of ONPO, which will facilitate future gene cloning and genetic improvement for enhancing seed yield in oilseed rape.